(untitled) (Palimpsesto, 2016)
At the end of 1965, the Che Guevara sent a "Message" to the fifth meeting of the Conference for the Solidarity of the Peoples of Africa, Asia and Latin America, better known as the Conference Tricontinental, carried out in Cuba in January of 1966. In his explicit celebration to the violence, the words of the Che encased the language and the strategy of what was called the " New Left side ". Nevertheless, the Conference Tricontinental did not manage to anticipate the agitation that there would provoke the university movements of 1968, which connected called of Guevara towards "Two, three, many Vietnam" with a different and own component of the sensibility of the New Left side: the alternative disrespect against the ideological inflexibility of all kinds. This work examines brief the genealogy and the geopolitical conflicts that surrounded the putting in scene of the Conference Tricontinental of 1966, putting special emphasis in the role of Lázaro Cárdenas, revolutionary Mexican ex-president.